Antibacterial activity of a new class of tris homoleptic Ru (II)‐complexes with alkyl‐tetrazoles as diimine‐type ligands. (28th May 2020) - Monti, Nicola; Zacchini, Stefano; Massi, Massimiliano; Hochkoeppler, Alejandro; Giorgini, Loris; Fiorini, Valentina; Stefan, Alessandra; Stagni, Stefano
Abstract : Herein, we describe a new family of tris chelate homoleptic Ru (II) complexes, [Ru(N^N) 3 ] 2+, where the role of the diimine‐type ligands (N^N) was fulfilled by 2‐pyridyl (PTZ) or 2‐quinolyl tetrazole (QTZ) derivatives decorated with various alkyl substituents at the N‐2 position of the tetrazole ring. The new Ru (II) complexes with general formula [Ru (PTZ‐R) 3 ] 2+ and [Ru (QTZ‐R) 3 ] 2+, were obtained as mixtures of facial ( fac ) and meridional ( mer ) isomers, as suggested by NMR ( 1 H, 13 C) experiments, and confirmed in the case of mer ‐[Ru (QTZ‐Me) 3 ] 2+, by X‐ray crystallography. The photophysical behavior of the tetrazole‐based [Ru(N^N) 3 ] 2+ type species was investigated by UV–vis absorption spectroscopy, providing trends typical of polypyridyl Ru (II) complexes. The new homoleptic complexes fac/mer ‐[Ru (PTZ‐R) 3 ] 2+ and fac/mer ‐[Ru (QTZ‐R) 3 ] 2+ have been assessed for any eventual antimicrobial activity towards two different bacteria such as Gram‐negative Escherichia coli and Gram‐positive Deinococcus radiodurans. Whereas being inactive toward E. coli, the response of agar disks diffusion tests suggested that some of the new fac/mer Ru (II) complexes could inhibit the growth of D. radiodurans. This effect was further investigated by determining the growth kinetics in liquid medium of D. radiodurans exposed to the fac/mer ‐[Ru (PTZ‐R) 3 ] 2+ and fac/mer ‐[Ru (QTZ‐R) 3 ] 2+ complexes at different concentrations. The outcome of these experiments highlighted that the turn‐on of the growth inhibitory effect took place as the linear hexyl chain was appended to the PTZ or QTZ scaffold, suggesting also how the inhibitory activity appeared more pronouncedly exerted by the facial isomers fac‐ [Ru (PTZ‐Hex) 3 ] 2+ and fac‐ [Ru (QTZ‐Hex) 3 ] 2+ (MIC = ca. 3.0 μg/ml) with respect to the corresponding meridional isomers (MIC = ca. 6.0 μg/ml). Abstract : New "fully tetrazole" Ru(II) complexes with general formula fac/mer ‐[Ru(PTZ‐R)3] 2+ and fac/mer ‐[Ru(QTZ‐R)3] 2+ are investigated as antimicrobials. Our results highlight that the introduction of an hexyl chain (R = Hex) in the structure of the Ru(II) complexes determines the good (MIC = 6.0 mg/mL) to excellent (MIC = 3.0 mg/mL for fac isomers) antibacterial effect toward Gram positive Deinococcus radiodurans, a not pathogenic bacterium that is listed among the toughest microorganisms, highly resistant to radiation and oxidative stress.